Clinical usefulness of Edinburgh CT criteria in patients with lobar intracerebral hemorrhage. (March 2021) - Ornello, Raffaele; Colangeli, Enrico; Tommasino, Emanuele; Tiseo, Cindy; Perrotta, Giulia; Scarpato, Ciro; Gentile, Martina; Mammarella, Leondino; Marini, Carmine; Pistoia, Francesca; Splendiani, Alessandra; Sacco, Simona
Background: Identifying the cause of intracerebral hemorrhage (ICH) is relevant to optimize its management. We aimed to assess the applicability and utility of the Edinburgh CT criteria for cerebral amyloid angiopathy (CAA) in an unselected cohort of hospitalized patients. Patients and Methods: We retrospectively applied the Edinburgh criteria to the first available brain CTs of patients hospitalized for a first-ever lobar ICH in the district of L'Aquila from 2011 to 2017. ICH characteristics and outcomes were compared according to the presence of the Edinburgh CT criteria, including associated subarachnoid hemorrhage (aSAH) and finger-like projections (FLPs). The outcome of ICH in-hospital mortality was assessed with multivariate logistic regression analysis. We adopted the Edinburgh criteria, age, NIHSS and Glasgow Coma Scale scores, systolic blood pressure, antiplatelet treatment, ICH volume, and intraventricular extension on admission as covariates. Results: Of 178 patients with lobar ICH, 52 (29.2%) had aSAH+FLPs, 60 (33.7%) aSAH only, 1 (0.6%) FLPs, and 65 (36.5%) none. Patients with aSAH+FLPs were older (79.0 ± 9.2 years) than those with only one criterion or none (74.0 ± 15.3 and 72.2 ± 13.8 years, respectively; P = 0.020). Patients with aSAH+FLPs also had more severe ICH at onset, higher in-hospital case-fatality (log rank test P = 0.003) and higher mRS scores at discharge (P < 0.001) as compared to those fulfilling one or none of the Edinburgh criteria. Low Glasgow Coma Scale score was the only factor independently associated to in-hospital case-fatality (odds ratio per point increase 0.51; 95% confidence interval, 0.32–0.91; P = 0.021). Discussion: Our data suggest the applicability of the Edinburgh CT criteria in a hospital setting. The presence of those criteria reflects ICH clinical severity. Conclusions: Applying the Edinburgh CT criteria might help refining the diagnosis and improving the management of patients with lobar ICH.